Impact of smoking and obesity on rheumatic disease in persons of productive age - Tana, Lusianawaty; Mutiatikum, Daroham (Universa Medicina, 2010)
Arthritis is a disease of the joints that causes pain and musculoskeletal stiffness, and may cause limitation of joint movement. Age, obesity, smoking behavior, and occupation are risk factors for rheumatic diseases. The objective of the present study was to evaluate the role of body mass index (BMI), smoking behavior, and occupation on rheumatic disease among persons of productive age in Indonesia. A cross-sectional study was conducted using National Basic Health Research data. The inclusion criterion was age 15-64 years. Rheumatic disease diagnosis was based on interview results and was defined as the presence of a history of rheumatic disease diagnosed by health professionals and/or rheumatic symptoms in the past 12 months. The study sample consisted of 609.097 persons who fulfilled the inclusion criterion. Compared to persons with normal BMI, rheumatic disease was more prevalent in the overweight (OR 1.25; 95%CI 1.21â1.29) and the obese (OR 1.52; 95%CI 1.47â1.56), but less prevalent in the underweight (OR 0.91; 95%CI 0.88â0.93). Compared to non-smokers, rheumatic disease was more prevalent in every day smokers (OR 1.65; 95%CI 1.60â1.70), occasional smokers (OR 1.41; 95%CI 1.35â1.47), and ex-smokers (OR 1.85; 95%CI 1.76â1.95). Measures for prevention of rheumatic disease are needed, e.g. through education to increase knowledge about the impact of smoking and obesity on rheumatic disease.